2007
DOI: 10.14214/sf.291
|View full text |Cite
|
Sign up to set email alerts
|

The impact of over-exploitation on the genetic structure of Turkish red pine (Pinus brutia Ten.) populations determined by RAPD markers

Abstract: tion on the genetic structure of Turkish red pine (Pinus brutia Ten.) populations determined by RAPD markers. Silva Fennica 41(2): 211-220. To determine the possible impact of over-exploitation on the genetic structure of Turkish red pine (Pinus brutia Ten.) populations, three natural and three over-exploited (human degraded) populations of the species in the Mediterranean region of Turkey were investigated with Randomly Amplified Polymorphic DNA (RAPD). With the 80 RAPD primers tested, 12 of them yielded 137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
3
16
2
3
Order By: Relevance
“…Overall heterozygosity (H t = 0.40) and overall heterozygosity within populations (H s = 0.40) is compatible with other studies on P. brutia (Icgen et al, 2006;Lise et al, 2007;Kandemir et al, 2004). However, genetic differentiation coefficient (Gst) values were between 1% and 5% in this study, while G ST ranged from 7% to 35% in previously reported RAPD studies on P. brutia (Icgen et al, 2006;Lise et al, 2007;Kandemir et al, 2004;Velioglu et al, 2002).…”
Section: Comparison Of Genetic Diversity Parameterssupporting
confidence: 91%
See 4 more Smart Citations
“…Overall heterozygosity (H t = 0.40) and overall heterozygosity within populations (H s = 0.40) is compatible with other studies on P. brutia (Icgen et al, 2006;Lise et al, 2007;Kandemir et al, 2004). However, genetic differentiation coefficient (Gst) values were between 1% and 5% in this study, while G ST ranged from 7% to 35% in previously reported RAPD studies on P. brutia (Icgen et al, 2006;Lise et al, 2007;Kandemir et al, 2004;Velioglu et al, 2002).…”
Section: Comparison Of Genetic Diversity Parameterssupporting
confidence: 91%
“…However, genetic differentiation coefficient (Gst) values were between 1% and 5% in this study, while G ST ranged from 7% to 35% in previously reported RAPD studies on P. brutia (Icgen et al, 2006;Lise et al, 2007;Kandemir et al, 2004;Velioglu et al, 2002). The high differentiation rate of those studies could be explained by various reasons; such as using seed stands, seed orchards and/or plantations which are geographically isolated and established far away from each other, low pollination mechanism between seed stands and/or seed orchards, mating system of species, and low seed distribution range and low level of gene flow between seed stands and seed orchards (Kang et al, 2001).…”
Section: Comparison Of Genetic Diversity Parameterscontrasting
confidence: 69%
See 3 more Smart Citations